A day of sun and serenity: picnic at Pulau Kapas, Terengganu / Farhan Faat … [et al.] - Faat, Farhan; Badiuzaman, Ahmad Fauzan; Mazlan, Nor Hafizah; Alden, Sperico Michael (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
An enchanting journey commences as the sun's rays whimsically scatter across the sea. With the help of Mak Cik Gemuk boat service and crew, we discover the tranquil Terengganu Island of Pulau Kapas, where the soothing embrace of nature is practically tangible. This little island is ideal for a day excursion due to its picturesque tropical setting, beautiful beaches, and pristine waters.